Sport specific adaptation in scapular upward rotation in elite golfers - Mackenzie, T. A.; Herrington, L.; Funk, L.; Horlsey, I.; Cools, A. (Journal of Athletic Enhancement, 2015)
Objective: Appropriate scapula position is necessary to optimise maximum force generation during the golf swing. Abnormalities in upward scapular rotation have been associated with various shoulder pathologies. Assessment of scapular position is considered an important clinical measure for sports therapists and trainers to prevent injury. This study investigated scapular upward rotation in elite golfers. Method: Forty five male golfers on European Challenge Tour and thirty six non-sportsman control volunteers met the inclusion criteria for the study. With the participant standing, the Palmmeter was used to measure lateral distances of the scapula from the spine and these measurements were used in the sin rule to calculate scapular rotation in the coronal plane. Result: The dominant scapula of controls was more upwardly rotated in both neutral (p=0.04, paired t-test) and in 60 degrees of shoulder abduction (p=0.04, paired t-test). The dominant scapula of golfers was significantly more upwardly rotated in neutral (p=0.01, paired t-test) and the lead scapula was significantly more upwardly rotated in 60° of shoulder abduction (p=0.01, paired t-test). Conclusion: Asymmetry of scapular rotation in the coronal plane in golfers as an indicator of risk in the golfers shoulder is not appropriate during screening. When compared with controls, golfers had a unique pattern of scapular upward rotation during arm abduction to 60°.